Building effective systems for the implementation of early childhood best practices - Argente-Tormo, Julia; Martinez Rico, Gabriel; Cañadas-Perez, Margarita; Bañuls-Lapuerta, Francesc Antoni (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Early childhood, understood as the services that attend children with disabilities or at risk of presenting developmental difficulties and their families, have been evolving towards recommended practices based on scientific evidence. These practices are determined by the importance of the family and natural environments as developmental contexts. However, scientific evidence shows that the construction of a system is required for an adequate implementation of these practices. The purpose of this work is to characterize the scientific research by identifying the main authors, articles and topics and to propose future research for their.